A hybrid PV-battery/diesel electricity supply on Peucang island: an economic evaluation - Matthias Günther (National Research and Innovation Agency, 2016)
Renewable energy technologies are currently under a dynamic cost development. This case holds especially for solar technology that has reached price levels that were unimaginable until a short time ago. It also holds for battery technologies the application of which is related to the increasing usage of photovoltaic energy converters and the growing interest in electric vehicles. With the decreasing prices more and more possible application cases of renewable energy technologies become economically viable. A case study was done for a location on a small island located on the west tip of Java. The levelized electricity cost of a hybrid electricity supply system composed of a solar generator and battery in combination with the existing diesel generators was compared to the electricity generation cost of the existing system. Two different battery options were taken into account, lead-acid batteries and lithium-ion batteries. The results of this study can give a rough orientation also for other locations with similar characteristics.